Perlukah Sistem Nilai Tukar Free Float Dipertahankan - E. Koestandar (Bina Nusantara University, 2001)
Article discuss the necessary in keeping free float exchange rate system that consist of exchange rate system, stock market, and crisis on rupiah exchange rate system. It also explain comparison of flexible exchange rate and fixed exchange rate.